Contribution to the physical study of the tablets: hardness tests. II. Test of self-made tablets - Herráez, M.; Suñé, J.Mª. (Ars Pharmaceutica (Internet), 1967)
In this second communication on the physical study of tablets, the weight and hardness of tablets of different size, with or without diametrical cut, prepared with a different pressure and dosification, are tested, with the aim of selting the minimum number of trials to be made for reaching a statistically acceptable value and to establish the influence of the above mentioned factors on the hardness of the tablets. Likerwise, the test of erosionability with the Erweka disk and the turbula is studied, setting conditions of the number of tablets in each trial and the time duration for arriving at acceptable value.